Perinatal Outcome of Pregnant Women with RhD Sensitization: A Five-Year Cross-Sectional Study at a Tertiary Care Hospital in Ethiopia - Kureba AA; Gudu W; Mersha A; Jemal E; Abdosh AA (Dove Medical Press, 2023)
Abdulhakim Abdurahman Kureba,1 Wondimu Gudu,1 Anteneh Mersha,1 Elias Jemal,2 Abdulfetah Abdulkadir Abdosh1 1Department of Obstetrics and Gynecology, St. Paul's Hospital Millennium Medical College, Addis Ababa, Ethiopia; 2Department of Obstetrics and Gynecology, Haramaya University Hiwot Fana Comprehensive Specialized Hospital, Harar, EthiopiaCorrespondence: Abdulhakim Abdurahman Kureba, Department of Obstetrics and Gynecology, St. Paul's Hospital Millennium Medical College, 1271, Swaziland St, Addis Ababa, Ethiopia, Tel +251911937561, Email abdulhakim317@gmail.comBackground: Isoimmunization is a process of immunizing an antigen-negative pregnant individual with a paternally derived fetal antigen. Although the Rh systems contain many antigen subtypes (D, C, c, E, e), the RhD antigen is highly immunogenic. This research aimed to investigate the perinatal Outcome of pregnant women with RhD sensitization at St. Paul's Hospital Millennium Medical College (SPHMMC), Ethiopia.Methodology: A facility-based retrospective cross-sectional study was conducted on 98 pregnant women with RhD alloimmunization at SPHMMC from September 11, 2016, to September 10, 2021. SPSS 26 was used for data analysis. Descriptive statistics were utilized to assess the perinatal outcome of pregnant women with RhD alloimmunization. Fisher's exact test was used to determine which association, and a P value < 0.05 was considered statistically significant.Results: From the 98 pregnancies (06 - hydropic, 92 - non-hydropic) at high risk for fetal anemia, 45.9% of cases had MCA-PSV above 1.5MoM. Among these, 21.42% of all fetuses received an intrauterine transfusion. Forty-three IUTs were performed in 21 fetuses. The median number of transfusions per fetus was two. About 52.4% of the transfused fetuses had severe anemia, and 28.6% had moderate anemia. Prediction of MCA PSV ≥ 1.5MOM in diagnosing moderate-severe anemia in pregnant women with RhD sensitization 81%. General neonatal survival of alloimmunizations was 93.8%, 90.5% with IUT, 50% with hydrops fetalis, and 96.7% without hydrops.Conclusion: This research provides evidence that MCA PSV ≥ 1.5MoM is modest predictor of moderate-severe anemia in untransfused fetuses. This study was a step toward the development of more extensive and multicenter studies on the Perinatal Outcome of pregnant women with RhD sensitization in Ethiopia. Extra studies are needed to evaluate strategies for estimates of fetal anemia after blood transfusion as a result of the absence of information on the IUT database.Keywords: intrauterine transfusion, RhD alloimmunization, fetal hydrops, fetal anemia